2008
DOI: 10.1038/sc.2008.98
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of transanal irrigation versus conservative bowel management for spinal cord injury patients

Abstract: Study design: Cost-effectiveness analysis following international guidelines and taking the societal viewpoint. Objectives: To estimate the cost-effectiveness of transanal irrigation using a self-administered irrigation system when compared with conservative bowel management. Setting: A randomized clinical trial was conducted at five spinal centres situated in Denmark, Germany, Italy, United Kingdom and Sweden. Estimates of resources and unit costs were made for the German health care system. Methods: Efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 18 publications
3
39
0
3
Order By: Relevance
“…These encouraging results have been subsequently confirmed by an Italian multicenter study, which concluded it may be considered as the treatment of choice for this type of patients (145). Furthermore, this therapy is cost-effective when compared to conservative management (145,146).…”
Section: Efficacysupporting
confidence: 58%
“…These encouraging results have been subsequently confirmed by an Italian multicenter study, which concluded it may be considered as the treatment of choice for this type of patients (145). Furthermore, this therapy is cost-effective when compared to conservative management (145,146).…”
Section: Efficacysupporting
confidence: 58%
“…51 Although product-related costs were higher with TAI, this was offset by lower costs for a caregiver to help with bowel management and changes/washing due to leakage, as well lower costs associated with urinary tract infections, and less time spent by the patient on bowel management. 51 …”
Section: Tai Systemsmentioning
confidence: 99%
“…Although gender, predominant symptom and colonic transit time were significantly associated with successful outcome, we would not recommend patient selection for TAI based only on these parameters. As TAI is a reversible safe treatment that enhances QoL both short term 18 and long term and has also recently been shown to be cost-effective for society compared with conservative bowel management, 22 we suggest that a trial and error strategy for the introduction of TAI to patients with NBD is used until more solid knowledge about factors associated with a positive outcome of TAI is gained from a prospective multicentre database. However, to some patients it may be an advantage to choose surgical treatment modalities earlier if significant practical problems with TAI are encountered.…”
Section: Side Effects In 75 Patientsmentioning
confidence: 99%